Synchronization of movements in group rhythmic gymnastics exercises - Medvedeva, E. N.; Davydova, A. Yu.; Zarodnyuk, G. V. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to complement and improve the group rhythmic gymnastics training system by a group routine synchronizing model with special technical and physical training elements.